2017
DOI: 10.1002/pd.5008
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards non‐invasive prenatal diagnosis among obstetricians in Pakistan, a developing, Islamic country

Abstract: Objectives Stakeholders' views are essential for informing implementation strategies for non‐invasive prenatal testing (NIPT). Little is known about such views in developing countries. We explored attitudes towards NIPT among obstetricians in Pakistan, a developing, Islamic country. Methods A 35‐item questionnaire was distributed and collected at eight events (a national conference and seven workshops in five cities) for obstetric professionals on advances in fetal medicine. Results Responses from 113 obstetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…We acknowledge the challenges in adopting such an approach to autonomous decisionmaking in populations with low literacy levels and where HCPs may believe they themselves lack knowledge of genetics and new technologies. 25 Therefore, to inform the development of practice guidelines on facilitating autonomous decision-making in Page 15 LMICs, research is needed on (i) how HCPs should facilitate decision-making, particularly in populations with low literacy levels and (ii) HCPs training needs to engage in shared decision-making about antenatal screening.…”
Section: Page 14mentioning
confidence: 99%
“…We acknowledge the challenges in adopting such an approach to autonomous decisionmaking in populations with low literacy levels and where HCPs may believe they themselves lack knowledge of genetics and new technologies. 25 Therefore, to inform the development of practice guidelines on facilitating autonomous decision-making in Page 15 LMICs, research is needed on (i) how HCPs should facilitate decision-making, particularly in populations with low literacy levels and (ii) HCPs training needs to engage in shared decision-making about antenatal screening.…”
Section: Page 14mentioning
confidence: 99%
“…Moving forward, options of minimally invasive autopsy 23 and non‐invasive prenatal diagnosis, particularly when performed prior to the period of ensoulment to permit timely TOP are investigations which Muslim communities appear to be open to 24 . In the era of prenatal next generation sequencing, more single gene disorders may be prospectively identified, 25,26 permitting knowledge of carrier status with testing strategies extending to those only requiring parental samples for lethal autosomal recessive conditions 27 .…”
Section: Discussionmentioning
confidence: 99%
“…During antenatal care, cfDNA screening could be done to find out congenital anomalies before the birth of the baby and to take required actions to lower the incidence of such congenital malformations. A study conducted in Pakistan regarding the perception and attitude of obstetric professionals towards implementing this test in Pakistan showed that 95% agreed with the necessity to diagnose genetic conditions as early as possible and 97% of the health professionals were in favour of providing prenatal screening tests [52].…”
Section: Significance Of Cfdna Screening In Pakistanmentioning
confidence: 99%